CyberKnife with Tumor Tracking: An Effective Treatment for High-Risk Surgical Patients with Single Peripheral Lung Metastases - Snider, James W.; Oermann, Eric K.; Chen, Viola J.; Rabin, Jennifer; Suy, Simeng; Yu, Xia; Vahdat, Saloomeh; Collins, Sean P.; Banovac, Filip; Anderson, Eric; Collins, Brian T. (Frontiers in Oncology, 2012)
Standard treatment for operable patients with single peripheral lung metastases is metastectomy. We report mature CyberKnife outcomes for high-risk surgical patients with biopsy proven single peripheral lung metastases. Twenty-four patients (median age 73 years) with a mean maximum tumor diameter of 2.5 cm (range, 0.8-4.5 cm) were treated over a 6-year period extending from September 2004 to September 2010 and followed for a minimum of 1 year or until death. A mean dose of 52 Gy was delivered to the prescription isodose line in 3 fractions over a 3 to 11 day period (mean, 7 days). At a median follow-up of 20 months, the 2-year Kaplan-Meier local control and overall survival rates were 87% and 50%, respectively. CyberKnife is an effective treatment for high-risk surgical patients with single small peripheral lung metastases. Trials comparing CyberKnife with metastectomy for operable patients are necessary to confirm equivalence.